Chemical composition and antioxidant activity of peanut skin extracts obtained from virginia and runner varieties - Barrionuevo, Guillermina (2015)
Fil: Barrionuevo, Guillermina. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Instituto de Ciencia y Tecnología de los Alimentos; Argentina.